A novel anaerobic down‐flow structured‐bed reactor for long‐term stable H2 energy production from wastewater. Issue 5 (14th July 2015) - Anzola‐Rojas, Mélida del Pilar; Zaiat, Marcelo
Abstract: BACKGROUND: Anaerobic, upflow fixed‐bed reactors have been considered suitable for the production of H2 from wastewater because, in contrast to completely mixed reactors, they avoid the washout of H2 ‐producing microorganisms. However, the excessive growth and accumulation of biomass on the bed are unfavorable and cause a drastic drop in biogas production, even though the fermentative process in the liquid medium continues unimpeded. This paper proposes a novel anaerobic fixed‐bed reactor configuration intended to control the accumulation of biomass by means of structuring the bed longitudinally and inverting the flow (down‐flow). RESULTS: Three anaerobic, down‐flow structured‐bed reactors (ADSBRs) with different support materials for the attachment of microorganisms were operated continuously with and without frequent biomass discharges. The H2 flow was continuously maintained for 120 days, resulting in a volumetric production of 0.6 L H2 L −1 d −1 and a yield of 0.5 mol H2 mol −1 cs . Compared with the anaerobic, upflow fixed‐bed reactor, the ADSBR increased by 10% the natural removal of biomass induced by the effluent and decreased by 15% the accumulated biomass in the bed. CONCLUSION: Hence, this study demonstrates that the ADSBR produces H2 continuously and stably due to the constant renewal of biomass; furthermore, young biomass exhibited more H2 ‐producing microorganisms than either non‐producing or H2 ‐consuming microorganisms. © 2015 Society of Chemical Industry